BACTERIAL AND FUNGAL PATHOGENS IN THE TRANSPLANTATION AND DIALYSIS CENTER. ANALYSIS FOR EIGHTEEN YEARS (1998–2015) - A. V. Vatazin; A. B. Zulkarnaev; E. V. Rusanova; N. E. Budnikova (Вестник трансплантологии и искусственных органов)
Aim: to analyze the dynamics of the microflora and its sensitivity to antibiotics in patients of dialysis and transplantation center.Materials and methods. We have examined the bacteriological test results of 1282 patients with chronic kidney disease, stage 5 (renal transplant recipients and dialysis patients) in 1998–2015: 1998–2003 («2003» period), 2008–2011 («2011» period) and 2012–2015 («2015» period). Biomaterial: urine, blood, wound effluent, sputum.Results. The incidence (share of all samples) of gram «–», gram «+» and fungi was 38, 56, 7% for «2003» period; 48, 69, 13% for «2011» period; 61, 54, 18% for «2015» period. The incidence of gram «–» in blood has significantly increased: 22% in «2003», 13% in «2011», and 45% in «2015», respectively. The incidence of Candida fungi is growing in sputum and urine: 15, 33, 41% and 8, 14, 18% (in 2003, 2011, 2015 respectively). The species composition of the fl ora has also significantly changed. In «2003» the shares of Staphylococcus spp. and Enterococcus spp. were 50 and 33%, in «2015» – 34 and 53% respectively. The shares of E. coli, Klebsiella spp., P. aeruginosa and Acinetobacter spp. were in «2003» 32, 21, 15, 11% respectively, and in «2015» – 17, 32, 9, 22%, respectively. The share of a «problem» genus of Candida: C. glabrata and C. krusei has significantly increased. Their combined share increased from 26 to 38% (2003–2015). There was a significant increase in antibiotic resistance, which is mostly pronounced in Enterococcus spp., Klebsiella spp. and Acinetobacter spp. All gram «+» bacteria in «2003» were susceptible to vancomycin and linezolid, but in «2015» 6% of Enterococcus were resistant to vancomycin. Conclusion. Bacterial profile has significantly changed. Regular analysis of the bacterial fl ora is necessary due to the growing antibiotic resistance.